Analisis Peramalan Permintaan Cireng Untuk Menentukan Jumlah Produksi Yang Optimal Dengan Metode Time Series: (Studi Kasus Pada Usaha Cireng Aneka Rasa Banjarnegara) - Desky Arlintyanda (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to determine the difference between demand forecasting to determine the optimal production amount without the Time Series Method using the Time Series Method at the Cireng Aneka Rasa Banjarnegara Business. The research method used is a combination method approach. The data used are primary and secondary data obtained directly from the owner of the Cireng Aneka Rasa Banjarnegara business. In the form of product demand data for the period January 2018 - December 2020. The calculation analysis of this study uses the Moving Average, Exponential Smoothing method with the help of the POM-QM for Windows V5 application so that it is known which method to determine the optimal amount of production for the company. The results of the comparative analysis of the exponential smoothing method are recommended for companies because it has the lowest error rate compared to the moving average method. Based on the results of the study, it is known that there is no significant difference between without the Time Series method and using the Time Series method. Therefore, the owner of the Cireng Aneka Rasa Banjarnegara business must be able to predict the amount of production so that it is optimal.